Ion exchange membrane with high proton conductivity and preparation method thereof
By using microporous membranes and composite materials of modified tourmaline, modified gas silicon, modified soy protein isolate and perfluorosulfonic acid resin in the ion exchange membrane, proton conduction caused by improved mechanical properties in the prior art is solved. The problem of rate reduction achieves a combination of high proton conductivity and high mechanical properties.
Patent Information
- Application Number
- CN202411469014.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While the existing ion exchange membranes improve mechanical properties, the proton conductivity is affected, making it difficult to achieve high proton conductivity and high mechanical properties at the same time.
Using microporous membranes as support materials, combined with modified nano tourmaline, modified gas silicon and modified soy protein isolate and perfluorosulfonic acid resin, composite membranes are prepared through plasma treatment and solution casting processes to form high proton conductivity ion exchange membrane.
The proton conductivity and mechanical properties of the ion exchange membrane are significantly improved, the stability and aging resistance of the membrane are enhanced, and the state is close to the superconductor.
Smart Images

Figure CN119119756A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ion exchange membranes, and in particular relates to an ion exchange membrane with high proton conductivity and a preparation method thereof. Background Art
[0002] Ion exchange membrane is a thin film that selectively transmits ions. It is widely used in the fields of separation of substances, desalination of seawater and brackish water, electrodialysis, fuel cells, liquid flow energy storage batteries and supercapacitors.
[0003] In order to improve the mechanical properties of ion exchange membranes, microporous membranes are generally used as reinforcing materials in the prior art, and then ion exchange resins are distributed on the surface of the microporous membranes. On the one hand, the matrix reinforcement layer can be made ultra-thin, which greatly reduces the proton conduction resistance, reduces ohmic polarization, and improves the power density of the battery stack; on the other hand, the matrix membrane becomes thinner while still having high mechanical strength, which can play a good reinforcing role for the perfluorosulfonic acid proton exchange membrane and improve the durability and mechanical stability of the composite proton exchange membrane. However, due to the introduction of a non-proton conductor microporous membrane, the proton conductivity of the composite membrane is reduced to a certain extent. How to prepare an ion exchange membrane with high proton conductivity and high mechanical properties is a problem that needs to be solved urgently. Summary of the invention
[0004] The present invention provides an ion exchange membrane with high proton conductivity, aiming to solve the above problems.
[0005] The present invention is achieved in this way: an ion exchange membrane with high proton conductivity, which uses a microporous membrane as a supporting material and also contains a composite material. The composite material includes the following raw materials in parts by weight: 2-5 parts of modified nano-tourmaline, 1-3 parts of modified gas silica, 1-2 parts of modified soy protein isolate, and 90-110 parts of perfluorosulfonic acid resin.
[0006] Preferably, the composite material comprises the following raw materials in parts by weight: 2.5-4.5 parts of modified nano-tourmaline, 1.5-2.5 parts of modified silica, 1.2-1.8 parts of modified soy protein isolate, and 95-105 parts of perfluorosulfonic acid resin.
[0007] Preferably, the composite material comprises the following raw materials in parts by weight: 3.5 parts of modified nano-tourmaline, 2 parts of modified silica, 1.5 parts of modified soy protein isolate, and 100 parts of perfluorosulfonic acid resin.
[0008] Preferably, the preparation method of the modified nano-tourmaline is as follows: 3-6 parts of nano-tourmaline are taken by weight, 10-15 parts of magnesium sulfate solution with a concentration of 40-50% are added, mixed, stirred for 30-50 minutes, filtered, placed in a muffle furnace and programmed to 500-600°C, and then placed in -40°C for freezing for 50-60 minutes; placed in a muffle furnace again and programmed to 700-800°C, then 10-20 parts of water and 1-2 parts of polyethylene glycol are added, treated with 60-80MHz ultrasound for 20-30 minutes, filtered, placed at 80-100°C for drying for 1-2 hours, and evenly spread on a low-temperature plasma treatment device The modified tourmaline is obtained by treating the nano-tourmaline with magnesium sulfate for 30-40 minutes. The nano-tourmaline is firstly treated with magnesium sulfate to be exfoliated and dispersed into finer grains. The nano-tourmaline is broken into smaller grains by heating-freezing-heating. Polyethylene glycol is added and ultrasonic treatment is performed to improve the dispersibility of the nano-tourmaline. The surface of the nano-tourmaline is rougher and the specific surface area is further increased by low-temperature plasma treatment to form a three-dimensional network space, thereby improving the adsorption and adsorbing more ion exchange resins, and forming a stable system with other components. The mechanical properties and proton conductivity of the ion exchange membrane can be improved by adding the modified nano-tourmaline.
[0009] Preferably, the low-temperature plasma treatment is carried out under the conditions of a power frequency of 15-20kHz, an operating voltage of 25-35kV, and a discharge power of 85-95W.
[0010] Preferably, the preparation method of the modified gas silicon is as follows: 3-5 parts of fumed silica are taken by weight, and then 15-20 parts of hypochlorous acid with a mass fraction of 5-10% are added, pressurized to 1-2atm in a closed container, heated in a water bath at 30-35°C and fully stirred for 5-10min, depressurized after cooling, and then filtered and washed with deionized water for 3 times, dried at 80-100°C, and the dried fumed silica is placed in tetramethyltetravinylcyclotetrasiloxane vapor, contacted and reacted in a fluidized bed for 30-50min to obtain modified gas silicon. By adding hypochlorous acid, heating and stirring, hypochlorous acid decomposes to produce oxygen and hydrochloric acid. Soaking in hydrochloric acid makes the fumed silica porous, impurities in the particle channels are dissolved, the channels are unblocked, the adsorption capacity is improved, and the generated oxygen forms small bubbles, enters the fumed silica, generates pressure, and creates more space on the inner wall, further improving the adsorption. It is further modified by tetramethyltetravinylcyclotetrasiloxane so that the modified fumed silica can be evenly dispersed in the system, improving the bonding ability of the fumed silica with the system, which is conducive to forming a network structure, and further improving the stability, mechanical properties, density, aging resistance, etc. of the ion exchange membrane.
[0011] Preferably, the preparation method of the modified soybean protein isolate is as follows: 3-6 parts of soybean protein isolate are taken by weight and sent into a low-temperature plasma generator for treatment for 3-5 minutes, the voltage of the low-temperature plasma generator is 85-95 kV, and the frequency is 100-120 Hz, then the soybean protein isolate treated with low-temperature plasma is added to 8-12 times the weight of water, and then 0.5-0.8 parts of sulfonated nano-carbon material are added, the temperature is raised to 40-50° C. and stirred for 30 minutes, and then ultrasonic-assisted dispersion is performed for 30 minutes, and the modified soybean protein isolate is dried at 50-60° C. to obtain the modified soybean protein isolate; first, the surface of the soybean protein isolate is bombarded with plasma energy to form a porous structure to improve the adsorption, and then the sulfonated nano-carbon material is added to fully combine with the soybean protein isolate to improve the proton conductivity of the soybean protein isolate, thereby improving the proton conductivity of the ion exchange membrane and improving the mechanical properties of the ion exchange membrane.
[0012] Preferably, the sulfonated nano-carbon material comprises sulfonated carbon nanotubes and sulfonated graphene, and the mass ratio of the two is 1:1-2.
[0013] The present invention also provides a method for preparing the above-mentioned ion exchange membrane with high proton conductivity, comprising the following steps:
[0014] The microporous membrane is subjected to plasma treatment, wherein the plasma treatment voltage is 60-80V, the current is 1-2A, and the treatment speed is 20-30cm / s. By plasma treatment of the microporous membrane, the specific surface area of the microporous membrane is further increased, and the microporous membrane can adsorb and tightly combine more composite materials;
[0015] The modified nano-tourmaline, the modified gas silica, the modified soy protein isolate and the perfluorosulfonic acid resin are mixed to prepare a solution;
[0016] The ion exchange membrane is obtained by composite membrane formation with a microporous membrane treated with plasma through a solution casting, spraying or dipping process.
[0017] Preferably, after the solution and the microporous membrane are composited into a membrane, ultraviolet irradiation treatment is applied for 10-20 minutes, and finally the membrane treated with ultraviolet irradiation is immersed in liquid nitrogen and frozen for 1-2 hours. The ultraviolet irradiation makes the composite material cross-linked, and each component fully plays its role, with stable performance and high energy density; freezing makes the ion exchange membrane increase its density at extremely low temperatures, approaching the superconductor state, and improving the proton conductivity.
[0018] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0019] The present invention prepares an ion exchange membrane through a microporous membrane and a composite material. By adding modified nano-tourmaline into the composite material, the mechanical properties and proton conductivity of the ion exchange membrane can be improved. By adding modified gas silica, the composite material can be evenly dispersed in the system, thereby improving the bonding ability of gas-phase silica with the system, which is conducive to forming a network structure and further improving the stability, mechanical properties, compactness, aging resistance and the like of the ion exchange membrane. By adding modified soy protein isolate, the proton conductivity of the ion exchange membrane is improved, and the mechanical properties of the ion exchange membrane are improved at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a flow chart for preparing an ion exchange membrane with high proton conductivity provided in Examples 1-5 of the present invention.
[0021] Figure 2 This is a flow chart for preparing an ion exchange membrane with high proton conductivity provided in Example 6 of the present invention. DETAILED DESCRIPTION
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.
[0023] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0024] Example 1
[0025] The present invention provides an ion exchange membrane with high proton conductivity. Figure 1 As shown, it uses a microporous membrane as a supporting material and also contains a composite material, wherein the composite material includes the following raw materials in parts by weight: 2 parts of modified nano-tourmaline, 1 part of modified gas silica, 1 part of modified soy protein isolate, and 90 parts of perfluorosulfonic acid resin;
[0026] The method for preparing the ion exchange membrane with high proton conductivity comprises the following steps:
[0027] The microporous membrane was subjected to plasma treatment, with a plasma treatment voltage of 60 V, a current of 1 A, and a treatment speed of 20 cm / s;
[0028] The modified nano-tourmaline, the modified gas silica, the modified soy protein isolate and the perfluorosulfonic acid resin are mixed to prepare a solution;
[0029] The ion exchange membrane is obtained by composite membrane formation with a microporous membrane treated with plasma through a solution casting, spraying or dipping process.
[0030] The preparation method of the modified nano tourmaline is as follows: 3 parts of nano tourmaline are taken by weight, 10 parts of magnesium sulfate solution with a concentration of 40% are added, the mixture is stirred for 30 minutes, filtered, placed in a muffle furnace and programmed to rise to 500°C, and then placed in ℃ and frozen for 50 minutes; placed in a muffle furnace again and programmed to rise to 700°C, and then 10 parts of water and 1 part of polyethylene glycol are added, treated with 60MHz ultrasonic waves for 20 minutes, filtered, placed at 80°C for drying for 1 hour, evenly spread on the ground electrode in a low-temperature plasma treatment device, and treated for 30 minutes under the conditions of a power frequency of 15kHz, a working voltage of 25kV, and a discharge power of 85W to obtain the modified tourmaline.
[0031] In this embodiment, the preparation method of the modified gas silicon is as follows: 3 parts of fumed silica are taken by weight, and then 15 parts of hypochlorous acid with a mass fraction of 5% are added, and the mixture is pressurized to 1 atm in a closed container, heated in a water bath at 30° C. and fully stirred for 5 minutes, and the pressure is released after cooling, and then filtered and washed with deionized water for 3 times, and dried at 80° C. The dried fumed silica is placed in tetramethyltetravinylcyclotetrasiloxane vapor, and contacted and reacted in a fluidized bed for 30 minutes to obtain modified gas silicon.
[0032] In a specific implementation, the preparation method of the modified soy protein isolate is as follows: 3 parts of soy protein isolate are taken by weight and sent into a low-temperature plasma generator for treatment for 3 minutes, the voltage of the low-temperature plasma generator is 85kV, and the frequency is 100Hz, and then the soy protein isolate treated with low-temperature plasma is added to 8 times the weight of water, and then 0.5 parts of sulfonated nano-carbon material is added, the temperature is raised to 40°C and stirred for 30 minutes, and then ultrasonic-assisted dispersion is performed for 30 minutes to obtain the modified soy protein isolate at 50, wherein the sulfonated nano-carbon material includes sulfonated carbon nanotubes and sulfonated graphene, and the mass ratio of the two is 1:1.
[0033] Example 2
[0034] The present invention provides an ion exchange membrane with high proton conductivity. Figure 1As shown, it uses a microporous membrane as a supporting material and also contains a composite material, wherein the composite material includes the following raw materials in parts by weight: 2.5 parts of modified nano-tourmaline, 1.5 parts of modified gas silica, 1.2 parts of modified soy protein isolate, and 95 parts of perfluorosulfonic acid resin;
[0035] The method for preparing the ion exchange membrane with high proton conductivity comprises the following steps:
[0036] The microporous membrane was subjected to plasma treatment, with a plasma treatment voltage of 60 V, a current of 1 A, and a treatment speed of 20 cm / s;
[0037] The modified nano-tourmaline, the modified gas silica, the modified soy protein isolate and the perfluorosulfonic acid resin are mixed to prepare a solution;
[0038] The ion exchange membrane is obtained by composite membrane formation with a microporous membrane treated with plasma through a solution casting, spraying or dipping process.
[0039] The preparation method of the modified nano tourmaline is as follows: 3 parts of nano tourmaline are taken by weight, 10 parts of magnesium sulfate solution with a concentration of 40% are added, the mixture is stirred for 30 minutes, filtered, placed in a muffle furnace and programmed to rise to 500°C, and then placed in ℃ and frozen for 50 minutes; placed in a muffle furnace again and programmed to rise to 700°C, and then 10 parts of water and 1 part of polyethylene glycol are added, treated with 60MHz ultrasonic waves for 20 minutes, filtered, placed at 80°C for drying for 1 hour, evenly spread on the ground electrode in a low-temperature plasma treatment device, and treated for 30 minutes under the conditions of a power frequency of 15kHz, a working voltage of 25kV, and a discharge power of 85W to obtain the modified tourmaline.
[0040] In this embodiment, the preparation method of the modified gas silicon is as follows: 3 parts of fumed silica are taken by weight, and then 15 parts of hypochlorous acid with a mass fraction of 5% are added, and the mixture is pressurized to 1 atm in a closed container, heated in a water bath at 30° C. and fully stirred for 5 minutes, and the pressure is released after cooling, and then filtered and washed with deionized water for 3 times, and dried at 80° C. The dried fumed silica is placed in tetramethyltetravinylcyclotetrasiloxane vapor, and contacted and reacted in a fluidized bed for 30 minutes to obtain modified gas silicon.
[0041] In a specific implementation, the preparation method of the modified soy protein isolate is as follows: 3 parts of soy protein isolate are taken by weight and sent into a low-temperature plasma generator for treatment for 3 minutes, the voltage of the low-temperature plasma generator is 85 kV, and the frequency is 100 Hz, and then the soy protein isolate treated with low-temperature plasma is added to 8 times the weight of water, and then 0.5 parts of sulfonated nano-carbon material is added, the temperature is raised to 40°C and stirred for 30 minutes, and then ultrasonic-assisted dispersion is performed for 30 minutes, and the modified soy protein isolate is dried at 50°C, wherein the sulfonated nano-carbon material includes sulfonated carbon nanotubes and sulfonated graphene, and the mass ratio of the two is 1:1.
[0042] Example 3
[0043] The present invention provides an ion exchange membrane with high proton conductivity. Figure 1 As shown, it uses a microporous membrane as a supporting material and also contains a composite material, wherein the composite material includes the following raw materials in parts by weight: 3.5 parts of modified nano-tourmaline, 2 parts of modified gas silica, 1.5 parts of modified soy protein isolate, and 100 parts of perfluorosulfonic acid resin;
[0044] The method for preparing the ion exchange membrane with high proton conductivity comprises the following steps:
[0045] The microporous membrane was subjected to plasma treatment, and the plasma treatment voltage was 70 V, the current was 1.5 A, and the treatment speed was 25 cm / s;
[0046] The modified nano-tourmaline, the modified gas silica, the modified soy protein isolate and the perfluorosulfonic acid resin are mixed to prepare a solution;
[0047] The ion exchange membrane is obtained by composite membrane formation with a microporous membrane treated with plasma through a solution casting, spraying or dipping process.
[0048] The preparation method of the modified nano tourmaline is as follows: 4.5 parts of nano tourmaline are taken by weight, 12.5 parts of magnesium sulfate solution with a concentration of 45% are added, the mixture is stirred for 40 minutes, filtered, placed in a muffle furnace, programmed to 550°C, and then placed in -40°C for freezing for 55 minutes; placed in a muffle furnace again, programmed to 750°C, and then 15 parts of water and 1.5 parts of polyethylene glycol are added, treated with 70MHz ultrasonic waves for 25 minutes, filtered, placed at 90°C for drying for 1.5 hours, evenly spread on the ground electrode in a low-temperature plasma treatment device, and treated for 35 minutes under the conditions of a power frequency of 18kHz, a working voltage of 30kV, and a discharge power of 90W to obtain the modified tourmaline.
[0049] In this embodiment, the preparation method of the modified gas silicon is as follows: 4 parts of fumed silica are taken by weight, and then 18 parts of hypochlorous acid with a mass fraction of 7.5% are added, pressurized to 1.5atm in a closed container, heated in a water bath at 32°C and fully stirred for 7 minutes, depressurized after cooling, and then filtered and washed with deionized water for 3 times, dried at 90°C, and the dried fumed silica is placed in tetramethyltetravinylcyclotetrasiloxane vapor, contacted and reacted in a fluidized bed for 40 minutes to obtain modified gas silicon.
[0050] In a specific implementation, the preparation method of the modified soy protein isolate is as follows: 4.5 parts of soy protein isolate are taken by weight and sent into a low-temperature plasma generator for treatment for 4 minutes, the voltage of the low-temperature plasma generator is 90 kV, and the frequency is 110 Hz, and then the soy protein isolate treated with low-temperature plasma is added to 10 times the weight of water, and then 0.65 parts of sulfonated nano-carbon material are added, the temperature is raised to 45°C and stirred for 30 minutes, and then ultrasonic-assisted dispersion is performed for 30 minutes, and the modified soy protein isolate is placed at 55°C for drying to obtain the modified soy protein isolate, wherein the sulfonated nano-carbon material includes sulfonated carbon nanotubes and sulfonated graphene, and the mass ratio of the two is 1:1.5.
[0051] Example 4
[0052] The present invention provides an ion exchange membrane with high proton conductivity. Figure 1 As shown, it uses a microporous membrane as a supporting material and also contains a composite material, wherein the composite material includes the following raw materials in parts by weight: 4.5 parts of modified nano-tourmaline, 2.5 parts of modified gas silica, 1.8 parts of modified soy protein isolate, and 105 parts of perfluorosulfonic acid resin;
[0053] The method for preparing the ion exchange membrane with high proton conductivity comprises the following steps:
[0054] The microporous membrane was subjected to plasma treatment, with a plasma treatment voltage of 80 V, a current of 2 A, and a treatment speed of 30 cm / s;
[0055] The modified nano-tourmaline, the modified gas silica, the modified soy protein isolate and the perfluorosulfonic acid resin are mixed to prepare a solution;
[0056] The ion exchange membrane is obtained by composite membrane formation with a microporous membrane treated with plasma through a solution casting, spraying or dipping process.
[0057] The preparation method of the modified nano tourmaline is as follows: 6 parts of nano tourmaline are taken by weight, 15 parts of magnesium sulfate solution with a concentration of 50% are added, the mixture is stirred for 50 minutes, filtered, placed in a muffle furnace, programmed to 600°C, and then placed in 40°C for freezing for 60 minutes; placed in a muffle furnace again, programmed to 800°C, and then added with 20 parts of water and 2 parts of polyethylene glycol, treated with 80MHz ultrasonic waves for 30 minutes, filtered, placed at 100°C for drying for 2 hours, evenly spread on the ground electrode in a low-temperature plasma treatment device, and treated for 40 minutes under the conditions of a power frequency of 20kHz, a working voltage of 35kV, and a discharge power of 95W to obtain the modified tourmaline.
[0058] In this embodiment, the preparation method of the modified gas silicon is as follows: 5 parts of fumed silica are taken by weight, and then 20 parts of hypochlorous acid with a mass fraction of 10% are added, and the mixture is pressurized to 2 atm in a closed container, heated in a water bath at 35° C. and fully stirred for 10 minutes, and the pressure is released after cooling, and then filtered and washed with deionized water for 3 times, and dried at 100° C. The dried fumed silica is placed in tetramethyltetravinylcyclotetrasiloxane vapor, and contacted and reacted in a fluidized bed for 50 minutes to obtain modified gas silicon.
[0059] In a specific implementation, the preparation method of the modified soy protein isolate is as follows: 6 parts of soy protein isolate are taken by weight and sent into a low-temperature plasma generator for treatment for 5 minutes, the voltage of the low-temperature plasma generator is 95 kV, and the frequency is 120 Hz, and then the soy protein isolate treated with low-temperature plasma is added to 12 times the weight of water, and then 0.8 parts of sulfonated nano-carbon material is added, the temperature is raised to 50°C and stirred for 30 minutes, and then ultrasonic-assisted dispersion is performed for 30 minutes, and the modified soy protein isolate is dried at 60°C to obtain the modified soy protein isolate, wherein the sulfonated nano-carbon material includes sulfonated carbon nanotubes and sulfonated graphene, and the mass ratio of the two is 1:2.
[0060] Example 5
[0061] The present invention provides an ion exchange membrane with high proton conductivity. Figure 1 As shown, it uses a microporous membrane as a supporting material and also contains a composite material, wherein the composite material includes the following raw materials in parts by weight: 5 parts of modified nano-tourmaline, 3 parts of modified gas silica, 2 parts of modified soy protein isolate, and 110 parts of perfluorosulfonic acid resin;
[0062] The method for preparing the ion exchange membrane with high proton conductivity comprises the following steps:
[0063] The microporous membrane was subjected to plasma treatment, with a plasma treatment voltage of 80 V, a current of 2 A, and a treatment speed of 30 cm / s;
[0064] The modified nano-tourmaline, the modified gas silica, the modified soy protein isolate and the perfluorosulfonic acid resin are mixed to prepare a solution;
[0065] The ion exchange membrane is obtained by composite membrane formation with a microporous membrane treated with plasma through a solution casting, spraying or dipping process.
[0066] The preparation method of the modified nano tourmaline is as follows: 6 parts of nano tourmaline are taken by weight, 15 parts of magnesium sulfate solution with a concentration of 50% are added, the mixture is stirred for 50 minutes, filtered, placed in a muffle furnace, programmed to 600°C, and then placed in 40°C for freezing for 60 minutes; placed in a muffle furnace again, programmed to 800°C, and then added with 20 parts of water and 2 parts of polyethylene glycol, treated with 80MHz ultrasonic waves for 30 minutes, filtered, placed at 100°C for drying for 2 hours, evenly spread on the ground electrode in a low-temperature plasma treatment device, and treated for 40 minutes under the conditions of a power frequency of 20kHz, a working voltage of 35kV, and a discharge power of 95W to obtain the modified tourmaline.
[0067] In this embodiment, the preparation method of the modified gas silicon is as follows: 5 parts of fumed silica are taken by weight, and then 20 parts of hypochlorous acid with a mass fraction of 10% are added, and the mixture is pressurized to 2 atm in a closed container, heated in a water bath at 35° C. and fully stirred for 10 minutes, and the pressure is released after cooling, and then filtered and washed with deionized water for 3 times, and dried at 100° C. The dried fumed silica is placed in tetramethyltetravinylcyclotetrasiloxane vapor, and contacted and reacted in a fluidized bed for 50 minutes to obtain modified gas silicon.
[0068] In a specific implementation, the preparation method of the modified soy protein isolate is as follows: 6 parts of soy protein isolate are taken by weight and sent into a low-temperature plasma generator for treatment for 5 minutes, the voltage of the low-temperature plasma generator is 95 kV, and the frequency is 120 Hz, and then the soy protein isolate treated with low-temperature plasma is added to 12 times the weight of water, and then 0.8 parts of sulfonated nano-carbon material is added, the temperature is raised to 50°C and stirred for 30 minutes, and then ultrasonic-assisted dispersion is performed for 30 minutes, and the modified soy protein isolate is dried at 60°C to obtain the modified soy protein isolate, wherein the sulfonated nano-carbon material includes sulfonated carbon nanotubes and sulfonated graphene, and the mass ratio of the two is 1:2.
[0069] Example 6
[0070] The present invention provides an ion exchange membrane with high proton conductivity. Figure 2 As shown, it uses a microporous membrane as a supporting material and also contains a composite material, wherein the composite material includes the following raw materials in parts by weight: 3.5 parts of modified nano-tourmaline, 2 parts of modified gas silica, 1.5 parts of modified soy protein isolate, and 100 parts of perfluorosulfonic acid resin;
[0071] The method for preparing the ion exchange membrane with high proton conductivity comprises the following steps:
[0072] The microporous membrane was subjected to plasma treatment, and the plasma treatment voltage was 70 V, the current was 1.5 A, and the treatment speed was 25 cm / s;
[0073] The modified nano-tourmaline, the modified gas silica, the modified soy protein isolate and the perfluorosulfonic acid resin are mixed to prepare a solution;
[0074] Composite membrane formation with plasma treated microporous membrane by solution casting, spraying or dipping process;
[0075] After the solution and the microporous membrane are composited into a membrane, the membrane is irradiated with ultraviolet light for 10-20 minutes, and finally the membrane after the ultraviolet light irradiation is immersed in liquid nitrogen and frozen for 1-2 hours to obtain an ion exchange membrane.
[0076] The preparation method of the modified nano tourmaline is as follows: 4.5 parts of nano tourmaline are taken by weight, 12.5 parts of magnesium sulfate solution with a concentration of 45% are added, the mixture is stirred for 40 minutes, filtered, placed in a muffle furnace, programmed to 550°C, and then placed in -40°C for freezing for 55 minutes; placed in a muffle furnace again, programmed to 750°C, and then 15 parts of water and 1.5 parts of polyethylene glycol are added, treated with 70MHz ultrasonic waves for 25 minutes, filtered, placed at 90°C for drying for 1.5 hours, evenly spread on the ground electrode in a low-temperature plasma treatment device, and treated for 35 minutes under the conditions of a power frequency of 18kHz, a working voltage of 30kV, and a discharge power of 90W to obtain the modified tourmaline.
[0077] In this embodiment, the preparation method of the modified gas silicon is as follows: 4 parts of fumed silica are taken by weight, and then 18 parts of hypochlorous acid with a mass fraction of 7.5% are added, pressurized to 1.5atm in a closed container, heated in a water bath at 32°C and fully stirred for 7 minutes, depressurized after cooling, and then filtered and washed with deionized water for 3 times, dried at 90°C, and the dried fumed silica is placed in tetramethyltetravinylcyclotetrasiloxane vapor, contacted and reacted in a fluidized bed for 40 minutes to obtain modified gas silicon.
[0078] In a specific implementation, the preparation method of the modified soy protein isolate is as follows: 4.5 parts of soy protein isolate are taken by weight and sent into a low-temperature plasma generator for treatment for 4 minutes, the voltage of the low-temperature plasma generator is 90 kV, and the frequency is 110 Hz, and then the soy protein isolate treated with low-temperature plasma is added to 10 times the weight of water, and then 0.65 parts of sulfonated nano-carbon material are added, the temperature is raised to 45°C and stirred for 30 minutes, and then ultrasonic-assisted dispersion is performed for 30 minutes, and the modified soy protein isolate is placed at 55°C for drying to obtain the modified soy protein isolate, wherein the sulfonated nano-carbon material includes sulfonated carbon nanotubes and sulfonated graphene, and the mass ratio of the two is 1:1.5.
[0079] Comparative Example 1: The difference from Example 3 is that the microporous membrane is not subjected to plasma treatment.
[0080] Comparative Example 2: The difference from Example 3 is that the modified nano-tourmaline is replaced by ordinary tourmaline.
[0081] Comparative Example 3: The difference from Example 3 is that the modified gas silicon is replaced by ordinary gas silicon.
[0082] Comparative Example 4: The difference from Example 3 is that the soy protein isolate is replaced by ordinary soy protein isolate.
[0083] Comparative Example 5: The difference from Example 3 is that the modified nano-tourmaline is replaced by ordinary tourmaline, the modified gas silica is replaced by ordinary gas silica, and the soy protein isolate is replaced by ordinary soy protein isolate.
[0084] Comparative Example 6: A commercially available ion exchange membrane.
[0085] Performance Testing
[0086] Tensile property test: The ion exchange membranes of Examples 1-6 and Comparative Examples 1-6 were tested according to GB / T 1040-2006 “Test method for tensile properties of plastics”.
[0087] Proton conductivity test: According to GB / T 20042.3-2009 "Proton exchange membrane fuel cell part 3: proton exchange membrane test method", the proton exchange membrane is tested by using an electrochemical impedance tester under the specified temperature and humidity conditions;
[0088] The test results are shown in the following table:
[0089]
[0090]
[0091] It can be seen from the above results that the ion exchange membrane prepared by the present invention has good mechanical properties and high proton conductivity. By adding modified nano-tourmaline, modified gas silica and modified soy protein isolate to the composite material, the three have a synergistic effect and can further improve the mechanical properties and proton conductivity of the ion exchange membrane.
[0092] It should be noted that, for the above embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the described order of actions, because according to the present invention, some steps may be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and modules involved are not necessarily required by the present invention.
[0093] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the scope of protection of the invention. Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. Based on these embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in this field can still combine, add, delete or make other adjustments to the features in the various embodiments of the present invention according to the circumstances without conflict, without making creative work, so as to obtain different other technical solutions that do not deviate from the concept of the present invention in essence, and these technical solutions also belong to the scope of protection of the present invention.
Claims
1. An ion exchange membrane with high proton conductivity, which uses a microporous membrane as a supporting material and also contains a composite material, characterized in that: The composite material comprises the following raw materials in parts by weight: 2-5 parts of modified nano-tourmaline, 1-3 parts of modified gas silica, 1-2 parts of modified soybean protein isolate and 90-110 parts of perfluorosulfonic acid resin.
2. The ion exchange membrane with high proton conductivity according to claim 1, characterized in that The composite material comprises the following raw materials in parts by weight: 2.5-4.5 parts of modified nano-tourmaline, 1.5-2.5 parts of modified gas silica, 1.2-1.8 parts of modified soybean protein isolate and 95-105 parts of perfluorosulfonic acid resin.
3. The ion exchange membrane with high proton conductivity according to claim 2, characterized in that The composite material comprises the following raw materials in parts by weight: 3.5 parts of modified nano-tourmaline, 2 parts of modified gas silica, 1.5 parts of modified soybean protein isolate, and 100 parts of perfluorosulfonic acid resin.
4. The ion exchange membrane with high proton conductivity according to claim 1, characterized in that The preparation method of the modified nano tourmaline is as follows: taking 3-6 parts of nano tourmaline by weight, adding 10-15 parts of magnesium sulfate solution with a concentration of 40-50%, stirring for 30-50 minutes, filtering, putting into a muffle furnace, heating to 500-600° C., and then freezing at -40° C. for 50-60 minutes; putting into the muffle furnace again, heating to 700-800° C., and then adding 10-20 parts of water and 1-2 parts of polyethylene glycol, treating with 60-80MHz ultrasonic wave for 20-30 minutes, filtering, drying at 80-100° C. for 1-2 hours, and evenly spreading on a ground electrode in a low-temperature plasma treatment device, treating for 30-40 minutes to obtain the modified tourmaline.
5. The ion exchange membrane with high proton conductivity according to claim 4, characterized in that The low-temperature plasma treatment is carried out under the conditions of power frequency of 15-20kHz, working voltage of 25-35kV and discharge power of 85-95W.
6. The ion exchange membrane with high proton conductivity according to claim 1, characterized in that The preparation method of the modified gas silicon is as follows: 3-5 parts of fumed silica are taken by weight, and then 15-20 parts of hypochlorous acid with a mass fraction of 5-10% are added, pressurized to 1-2atm in a closed container, heated in a water bath at 30-35°C and fully stirred for 5-10min, depressurized after cooling, and then filtered and washed with deionized water for 3 times, dried at 80-100°C, and the dried fumed silica is placed in tetramethyltetravinylcyclotetrasiloxane vapor, contacted and reacted in a fluidized bed for 30-50min to obtain the modified gas silicon.
7. The ion exchange membrane with high proton conductivity according to claim 6, characterized in that The preparation method of the modified soybean protein isolate is as follows: 3-6 parts of soybean protein isolate are taken by weight and sent into a low-temperature plasma generator for treatment for 3-5 minutes, the voltage of the low-temperature plasma generator is 85-95 kV, and the frequency is 100-120 Hz, then the soybean protein isolate treated with low-temperature plasma is added into 8-12 times the weight of water, then 0.5-0.8 parts of sulfonated nano-carbon material is added, the temperature is raised to 40-50° C. and stirred for 30 minutes, then ultrasonic-assisted dispersion is performed for 30 minutes, and the soybean protein isolate is dried at 50-60° C. to obtain the modified soybean protein isolate.
8. The ion exchange membrane with high proton conductivity according to claim 7, characterized in that The sulfonated nano-carbon material comprises sulfonated carbon nanotubes and sulfonated graphene, and the mass ratio of the two is 1:1-2.
9. The method for preparing an ion exchange membrane with high proton conductivity according to any one of claims 1 to 8, characterized in that: The steps include: Plasma treating the microporous membrane; The modified nano-tourmaline, the modified gas silica, the modified soy protein isolate and the perfluorosulfonic acid resin are mixed to prepare a solution; The ion exchange membrane is obtained by composite membrane formation with a microporous membrane treated with plasma through a solution casting, spraying or dipping process.
10. The method for preparing an ion exchange membrane with high proton conductivity according to claim 9, characterized in that: After the solution and the microporous membrane are composited into a membrane, the membrane is irradiated with ultraviolet light for 10-20 minutes, and finally the membrane after the ultraviolet light irradiation is immersed in liquid nitrogen and frozen for 1-2 hours.
